Analysis of Factors Affecting Investment Decision-Making in the Indonesian Capital Market - Barnabas Tridig Silaban; Ana Rusmardiana; Aldian Yusup; Nana Adriana; Gratia Tehilla Yustus (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
The Indonesian capital market has experienced significant investor growth, particularly among retail investors and younger generations. However, this increase in participation has not been fully accompanied by rational and high-quality investment decision-making. This study aims to analyze the factors influencing investment decision-making in the Indonesian capital market, with a particular focus on behavioral factors, financial literacy, and risk perception. The study employs a qualitative approach using a systematic literature review method, examining a curated sample of recent and relevant scholarly articles, academic books, and official institutional reports related to investment behavior and decision-making. The data were analyzed using descriptive qualitative analysis and content analysis to identify patterns and relationships among variables. The findings indicate that financial literacy is the most dominant factor in improving the quality of investment decisions, while overconfidence, herding behavior, and risk perception also significantly influence investor behavior. The interaction among these factors creates a complex pattern of investment decision-making. The novelty of this study lies in the development of an integrated analytical framework that simultaneously combines behavioral biases, financial literacy, and risk perception within a single model, particularly in the context of an emerging market such as Indonesia. This study contributes to the literature in three main ways. First, it provides a comprehensive synthesis of prior studies by integrating behavioral and cognitive perspectives into a unified framework. Second, it highlights the mediating role of risk perception and the moderating role of financial literacy in shaping investment decisions. Third, it offers contextual insights specific to the Indonesian capital market, where retail investor dominance and digital influence create unique behavioral dynamics. This study contributes theoretically by extending behavioral finance literature through a multidimensional perspective, and practically by providing insights for investors, regulators, and financial institutions to improve decision quality through a more holistic approach.